Factors Influencing Blind Adolescents' Reproductive Health Behaviors, in Sukabumi - Haryani, Hana; Mohd Said, Faridah; Syazana, Nur (KnE Social Sciences, 2023)
Adolescents with disabilities or special needs are very vulnerable to various health problems including reproductive health. In helping to maintain reproductive health, of course, there needs to be other factors that can support the achievement of reproductive health maintenance such as sources of information, knowledge, and attitudes. This study aims is to determine the influence of sources of information, knowledge, and attitudes toward the reproductive health of blind adolescents in the Sukabumi. A source of information is a set of useful information to meet the need for information or news for the wider community. Knowledge is the result of knowing and this happens after a person performs sensing of an object. Attitude is the readiness to react to an object in a certain environment as a passion for an object. Behavior is a person’s response or reaction to a stimulus. This type of research is correlational with the cross-sectional approach. Total sampling was used for the population and sample of 42 blind adolescents in Sukabumi. Statistical analysis was done using multiple linear regression. The results showed that there was a significant influence of information sources on the reproductive health behavior of blind adolescents (p-value 0.000), there was a relationship of knowledge on the reproductive health behavior of blind adolescents (p-value 0.000), and there was knowledge of attitudes toward reproductive health behaviors of blind adolescents (p-value 0.000). There is a simultaneous influence of sources of information, knowledge and attitudes towards reproductive health behaviors of blind adolescents (p-value 0.000). It can be concluded that sources of information, knowledge, and attitudes have an influence on the reproductive health behavior of adolescents with visual disabilities. This study’s findings can be used to further investigate reproductive health in blind adolescents. Keywords: adolescents, behavior, blind disability, knowledge, reproductive health, sources of information How